Ubiquitination as an Important Host-Immune Response Strategy in Penaeid Shrimp: Inferences From Other Species - Zhang, Zhaoxue; Aweya, Jude Juventus; Yao, Defu; Zheng, Zhihong; Tran, Ngoc Tuan; Li, Shengkang; Zhang, Yueling (Frontiers in Immunology, 2021)
Shrimp aquaculture is an essential economic venture globally, but the industry faces numerous challenges, especially pathogenic infections. As invertebrates, shrimp rely mainly on their innate immune system for protection. An increasing number of studies have shown that ubiquitination plays a vital role in the innate immune response to microbial pathogens. As an important form of posttranslational modification (PTM), both hosts and pathogens have exploited ubiquitination and the ubiquitin system as an immune response strategy to outwit the other. This short review brings together recent findings on ubiquitination and how this PTM plays a critical role in immune modulation in penaeid shrimps. Key findings inferred from other species would help guide further studies on ubiquitination as an immune response strategy in shrimp-pathogen interactions.